Gangguan Kepribadian Psikopatik Tokoh Utama Dalam Film Kokuhaku - Ratih Rahmawati; Budi Rukhyana; Mugiyanti Mugiyanti (Universitas Pakuan, 2021)
ABSTRACT: This research discusses the psychopathic personality disorder of the main character in the film Kokuhaku. This study aims to determine the psychopathic personality traits in the main character according to the theory of Robert D. Hare. The object of this research is the psychopathic personality disorder in the main character. The source of income data is obtained from the Kokuhaku film using the library research technique in the Kokuhaku film. This research draws references from supporting books, such as literature studies, fiction studies, personality psychology, and the internet.